(3JWhQ GdEYdGe hab JcfhdhLjG GdEJUGd GdMOjKs - (3Ydj YHO GdaJGM(B, (3cfYGfs ((3YeGf (B:s (3OGQ GdCjGe ddfTQ h GdJhRjY(B,s, 2015)
(3GdJWhQGJ GdYGdejI aj JcfhdhLjG GdGJUGd GdMOjKI h CKQgG Ydi hGbY hSGFd GdGYdGe GdGdcJQhfjI h GdJWhQGJ GdYGdejI aj JcfhdhLjG GdGJUGd GdMOjKI h CKQgG Ydi hGbY GdUMGaI GdeUQjI h Ydi GdLeghQ GdeUQj h GdYhdeI GdKbGajI cBdjI ef BdjGJ GdJWhQ GdJcfhdhLj GdMOjK h CNjQG CKQ JcfhdhLjG GdGJUGd GdMOjKI h GdYhdeI GdKbGajI Ydi GdKbGaI GdeUQjI (B.s
(3eQGLY U(B.171s
Keywords: (3hSGFd GdGYdGe (B- (3eUQs